SunShade: enabling software-defined solar-powered systems - Singh, Akansha; Lee, Stephen; Irwin, David; Shenoy, Prashant (2017 ACM IEEE 8th International Conference on Cyber Physical Systems (ICCPS), 2017)
The electric grid was not designed to support the large-scale penetration of intermittent solar generation. As a result, current policies place hard caps on the solar capacity that may connect to the grid. Unfortunately, users are increasingly hitting these caps, which is restricting the natural growth of solar power. To address the problem, we propose Software-defined Solar-powered (SDS) systems that dynamically regulate the amount of solar power that flows into the grid. To enable SDS systems, this paper introduces fundamental mechanisms for programmatically controlling the size of solar flows, including mechanisms to both enforce an absolute limit on solar output and a new class of Weighted Power Point Tracking (WPPT) algorithms that enforce a relative limit on solar output as a fraction of its maximum power point (MPP). We implement an SDS prototype, called SunShade, and evaluate tradeoffs in the accuracy and fidelity of these mechanisms to enforce limits on solar flows. For example, we quantify the effects of variable conditions, such as clouds, passersby, and other shading, on the fidelity of a search-based WPPT algorithm, which must periodically deviate from its cap to discover changes in the MPP that affect the cap's accuracy.